Kemampuan pemilikan perumahan bagi generasi Y - Md. Anuar, Farah Hanan (2014)
Most of the available research today focuses on housing affordability between different income groups, but very little work has been done on housing affordability for different generations. This research focuses on housing affordability for the young generation, otherwise known as generation Y. The strong economic growth in Malaysia over the last few decades have seen house prices increase at a rate that far exceeds the growth in real income. This disparity is particularly serious for the generation Y, due to their lower income, as they start out their working life away from the protection of their parents. To investigate this issue, an exploratory study has been conducted on a sample of generation Y employees living in Kuala Lumpur. data have been collected through questionnaires and interviews. The first objective of the study is to identify the main factors that influenced affordability among generation Y. The second objective is to study the relationship between demographic factors and housing affordability among generation Y. The results have been analysed using frequency analysis, likert scaling, cross tabulation and chi- square. The findings should that there is a significant correlation between demographic factors in determining affordable housing within Kuala Lumpur area. Demographic factors had the most significant relationship with income in influencing housing affordability among generation Y. This conclude that the different demographic factors would influence the housing market and the resulting different levels of ability.